Discrete-Time Valuation of American Options with Stochastic Interest Rates - Amin, Kaushik I.; Bodurtha, James N. (Review of Financial Studies, 1995)
We develop an arbitrage-free discrete time model to price American-style claims for which domestic term structure risk, foreign term structure risk, and currency risk are important. This model combines a discrete version of the Heath, Jarrow, and Morton (1992) term structure model with the binomial model of Cox, Ross, and Rubinstein (1979). It converges (weakly) to the continuous time models in Amin and Jarrow (1991, 1992). The general model is “path dependent” and can be implemented with arbitrary volatility functions to value claims with maturity up to five years. The model is illustrated with applications to long-dated American currency warrants and a cross-rate swap from the quanto class.